DNA sequencing reveals high arbuscular mycorrhizal fungi diversity in the rhizosphere soil of Prunus africana trees in fragmented Afromontane forests - Tchiechoua, Yves H.; Odee, David W.; Ngonkeu, Eddy L.M.; Kinyua, Johnson; Ngumi, Victoria W.; Machuka, Eunice M.; Waweru, Bernice; Le Roux, Marcellous; Pelle, Roger (Springer, 2023)
Arbuscular mycorrhizal fungi (AMF) play a key role in medicinal plant species, besides their ecological role in shaping plant communities. Knowledge about the diversity and structure of AMF communities associated with the endangered Prunus africana is valuable in the conservation and domestication of the species for its medicinal products.We investigated the diversity and structure of AMF species communities in the rhizosphere soils of P. africana trees occurring in four fragmented Afromontane forests found in Cameroon (Mount Cameroon and Mount Manengouba) and Kenya (Chuka and Malava) using Illumina Miseq sequencing of 18S rRNA gene amplicons.A total of 64 virtual taxa (VT) belonging to eight genera were detected, namely Glomus (43 VT), Claroideoglomus (6 VT), Paraglomus (5 VT), Acaulospora (4 VT), Diversispora (3 VT), and Archaeospora, Pacispora, and Scutellospora with 1 VT each. Scutellospora heterogama VTX00286 was the most abundant and common species in all four sites (49.62%). Glomeraceae and Gigasporaceae were the most abundant families found across the sites, while Acaulosporaceae, Pacisporaceae, and Archaeosporaceae were rare, represented by < 1% of all the detected taxa.Our data shows a high diversity of AMF species associated with P. africana and variable community structure partially shaped by local edaphic factors.